Synthesis and structural elucidation of a dehydrochloromethyltestosterone metabolite. Issue 14 (22nd March 2018) - Kratena, Nicolas; Pilz, Sarah M.; Weil, Matthias; Gmeiner, Günter; Enev, Valentin S.; Gärtner, Peter
Abstract : The identity of a human long-term metabolite of the doping agent Oral Turinabol (DHCMT) is secured by the synthesis of all probable stereoisomers. Abstract : The human urinary long-term metabolite "M3" (4-chloro-17β-hydroxymethyl-17α-methyl-18-norandrost-13-en-3-ol) of the common doping agent DHCMT has thus far been detected via GC/MS-MS, creating ambiguities concerning its absolute configuration. Its structure was elucidated via the synthesis of all eight possible stereoisomers with 17β-hydroxymethyl configuration. The highlights of the synthesis consist of a novel first generation approach to 4β-chloro-5β compounds as well as a divergent route which allows easy access to the remaining A-ring chlorohydrins.